Understanding consumer preferences for rice beans for enhanced food security: a choice experiment approach in western Kenya - Ayieko, David Michael Ochieng; Otieno, David Jakinda; Makokha, Stella; Oluoch-Kosura, Willis (Frontiers in Sustainable Food Systems, 2024)
Hidden hunger, a condition that arises from eating a low legume-cereal mix, hinders the attainment of food security. It affects 25% of the world’s population and 20% of the African population. To address this problem, various crop improvement programs aimed at increasing the introduction of biofortified beans in households’ diets have been initiated. However, Kenya still has a deficit in protein intake despite the availability of biofortified beans. In western Kenya, specifically Busia and Migori counties, where there is high consumption of staple cereals, rice beans (Vigna umbellata) have been piloted on farmers’ fields, but the extent of uptake at the consumption level remains undocumented. Therefore, this study analyzed consumer preferences for improved rice beans through a discrete choice experiment (DCE) approach. The results showed that consumers were willing to pay 166.59 Kenya Shillings (Ksh) for high protein content, Ksh 225.69 for red color, Ksh 113.46 for short cooking time, Ksh 202.30 for good legume-cereal mix and Ksh 139.29 for sweet taste. These findings have important implications for policy interventions on crop breeding, food processing, healthy food and nutrition guidelines.